Parir y nacer en tiempos de COVID-19 en Uruguay; Delivery and birth during covid-19 in Uruguay - Cherro, Victoria Evia Bertullo (Universidad Autónoma Metropolitana, 2021)
The purpose of the article is to analyze the structural dimensions of the social production of delivery and birth in the context of covid-19 in Uruguay, focusing on women’s experiences, based on the dialogue between critical medical anthropology and feminist anthropology. Through a qualitative and exploratory methodology, secondary data are linked to the interviews of eight women of medium-high socio-educational level. We conclude that their experiences, care trajec- tories and strategies deployed, were crossed by fears and uncertainties regarding respect for their enshrined rights during the care of pregnancy, childbirth and birth in the health services by appealing to arguments of exceptionality. This article contributes to the understanding of the cases’ continuities and exceptionalities, taking into account the variables of gender, class and nationality. Additionally, this article also contributes to the fruitful development of dialogues between both conceptual approaches.; El objetivo de este artículo es analizar las dimensiones estructurales de la producción social del parto y el nacimiento en el contexto de la covid-19 en Uruguay a partir del diálogo entre la antropología médica crítica y la antropología feminista, poniendo en el centro las experiencias de mujeres. Mediante una metodología cualitativa y exploratoria se relacionan datos secundarios con los relatos de ocho mujeres de nivel socioeducativo medio-alto. Se concluye que sus experiencias, trayectorias de atención y estrategias desplegadas estuvieron marcadas por los temores e incertidumbres en cuanto al respeto de los derechos consagrados durante la atención al embarazo, el parto y el nacimiento en los servicios de salud, pues estos últimos apelaban al argumento de excepcionalidad. Se aporta a la comprensión de continuidades y excepcionalidades del caso, considerando las variables de género, clase y nacionalidad, así como al fructífero desarrollo de diálogos entre la antropología médica crítica y la antropología feminista.